2011
DOI: 10.1371/journal.pone.0021978
|View full text |Cite
|
Sign up to set email alerts
|

Murine and Bovine γδ T Cells Enhance Innate Immunity against Brucella abortus Infections

Abstract: γδ T cells have been postulated to act as a first line of defense against infectious agents, particularly intracellular pathogens, representing an important link between the innate and adaptive immune responses. Human γδ T cells expand in the blood of brucellosis patients and are active against Brucella in vitro. However, the role of γδ T cells in vivo during experimental brucellosis has not been studied. Here we report TCRδ−/− mice are more susceptible to B. abortus infection than C57BL/6 mice at one week pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 54 publications
3
45
1
Order By: Relevance
“…However, we observed that TCR-d and TAP1 deficiency, but not MHCII deficiency, also affected early Brucella control in the lungs, suggesting that these cells could be a potential source of IL-17A in our model. In keeping with this observation, IL-17 production by g/d T cells was reported in a Brucella model (65) and in several other pulmonary infectious models (66)(67)(68).…”
Section: Discussionsupporting
confidence: 75%
“…However, we observed that TCR-d and TAP1 deficiency, but not MHCII deficiency, also affected early Brucella control in the lungs, suggesting that these cells could be a potential source of IL-17A in our model. In keeping with this observation, IL-17 production by g/d T cells was reported in a Brucella model (65) and in several other pulmonary infectious models (66)(67)(68).…”
Section: Discussionsupporting
confidence: 75%
“…The role of IL-17 + γδ T lymphocytes (and of IL-17) in infection, tumor immunity, and autoimmunity has been reported, and it is still controversial [50,[58][59][60][61][62][63]. A clear involvement of IL-17 + γδ T lymphocytes in autoimmunity has been evidenced in experimental arthritis and autoimmune encephalomyelitis, in which these cells have been shown to amplify CD4 + Th17 cell responses, to suppress Foxp3 + Treg cells, and to contribute to the development of the response [48,[62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the relevance of CCL25 in the context of allergic responses is correlated to IL-17 production in the allergic site. Whether this phenomenon contributes to the enhancement or regulation of allergy is still unclear, since contrasting roles for IL-17 have been described [54][55][56][57].The role of IL-17 + γδ T lymphocytes (and of IL-17) in infection, tumor immunity, and autoimmunity has been reported, and it is still controversial [50,[58][59][60][61][62][63]. A clear involvement of IL-17 + γδ T lymphocytes in autoimmunity has been evidenced in experimental arthritis and autoimmune encephalomyelitis, in which these cells .…”
mentioning
confidence: 99%
“…Early production of IFNg for activation of other T cells, dendritic cells, and macrophages is known to be a critical step during early host defense against pathogens and in particular against invading intracellular agents. 14,29 More work is needed to clarify the mechanisms of gd T-cell recruitment to and activation at infection sites and what potential roles they may play during development of adaptive immunity. This research represents an initial step toward potential identification of key factors mediating either success or failure of host immunity during intracellular infections and ultimately leading to pathogen clearance/healing or establishment of persistent infection, respectively.…”
Section: Discussionmentioning
confidence: 99%